N-Telopeptide of Type I collagen long-term dynamics in breast cancer patients with bone metastases: clinical outcomes and influence of extraskeletal metastases - Ferreira, Arlindo (2022)
© 2016 AlphaMed Press. This article is published and distributed under the terms of the Oxford University Press, Standard Journals Publication Model (https://academic.oup.com/journals/pages/open_access/funder_policies/chorus/standard_publication_model)